The Effect of Endometrial Thickness on Pregnancy, Maternal, and Perinatal Outcomes of Women in Fresh Cycles After IVF/ICSI: A Systematic Review and Meta-Analysis - Liao, Zhiqi; Liu, Chang; Cai, Lei; Shen, Lin; Sui, Cong; Zhang, Hanwang; Qian, Kun (Frontiers in Endocrinology, 2022)
Background: Thin endometrium on ovulation triggering day is associated with impaired pregnancy outcomes in women after in vitro fertilization/ intracytoplasmic sperm injection (IVF/ICSI), but the role of thick endometrium on pregnancy outcomes remains controversial. Moreover, there has been insufficient evidence currently to analyze the influence of endometrial thickness (EMT) on obstetric complications and neonatal outcomes. Thus, we performed this meta-analysis to evaluate the effect of EMT on pregnancy, maternal, and neonatal outcomes in an enlarged sample size. Methods: The databases Pubmed, Embase, Cochrane Libraries and Web of Science were searched for English articles evaluating the correlation between EMT and pregnancy, maternal, or neonatal outcomes in women who underwent IVF/ICSI. We included studies that depicted a clear definition of outcomes and EMT grouping on ovulation triggering day. The EMT effect was analyzed in fresh cycle. Qualities of studies were assessed by the Newcastle-Ottawa Scale (NOS). Odds ratios (ORs) and weighted mean difference (WMD) with 95% confidence intervals (CIs) were calculated for analyzing dichotomous and continuous outcomes respectively, under a fixed or random effect model. Results: 20 literatures were included for the final meta-analysis. A decreased trend towards pregnancy outcomes was observed, such as live birth rate (LBR), clinical pregnancy rate (CPR), and implantation rate (IR) in the thin endometrium groups (EMT< 7 mm). In contrast, thick endometrium (EMT> 14 mm) had no effect on pregnancy outcomes compared to medium EMT groups (EMT 7-14 mm). Moreover, thin endometrium (EMT< 7.5 mm) enhanced the incidence of hypertensive disorders of pregnancy (HDP) and small-for-gestational-age (SGA) infants, and dampened the birthweight (BW) of babies. Conclusions: Our studies indicated that thin endometrium not only had detrimental effect on pregnancy outcomes, but also increased the risk of HDP in women and SGA of babies, or decreased BW of babies. And the thick endometrium does not have adverse effects on IVF outcomes. Therefore, patients need to be informed possible obstetric complications and neonatal outcomes caused by thin endometrium and encouraged to actively cooperate with perinatal care.